Lethal prognosis of an infant with intraperitoneal large venous malformation - Kazutaka Ouchi, MD, PhD; Kunihiko Tsuchiya, MD, PhD; Tomoko Iehara, MD, PhD; Ayako Nishimura, MD, PhD; Eiichi Konishi, MD, PhD; Hajime Hosoi, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2021)
Intraperitoneal venous malformations are uncommon. Therefore, the prognosis of patients has not been determined, and appropriate treatments have not been established. We have reported the case of a neonate with an extensive intraperitoneal venous malformation. She did not have a developmental disorder nor a functional disability; thus, she was observed without treatment. However, the patient died suddenly of obstructive venous return disorder due to thrombosis in a vein draining from the venous malformation, followed by blood pooling in the expanding venous malformation. Extensive intraperitoneal venous malformations can be associated with a lethal prognosis owing to thrombosis. Anticoagulation therapy should be considered proactively for prophylaxis of thrombotic dysfunction.